2021
DOI: 10.3390/s21072292
|View full text |Cite
|
Sign up to set email alerts
|

Step Length Is a Promising Progression Marker in Parkinson’s Disease

Abstract: Current research on Parkinson’s disease (PD) is increasingly concerned with the identification of objective and specific markers to make reliable statements about the effect of therapy and disease progression. Parameters from inertial measurement units (IMUs) are objective and accurate, and thus an interesting option to be included in the regular assessment of these patients. In this study, 68 patients with PD (PwP) in Hoehn and Yahr (H&Y) stages 1–4 were assessed with two gait tasks—20 m straight walk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Rather, the severity of PD-specific motor symptoms seems true to inflict the walking performance in this and other PD cohorts. Specifically, under ST, the increase in motor symptoms explains a decrease in spatio-temporal walking parameters, e.g., gait speed, which is also consistent with previous studies ( 14 , 75 ). Moreover, our results suggest that patients with a walking aid are more affected by the underlying disease.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, the severity of PD-specific motor symptoms seems true to inflict the walking performance in this and other PD cohorts. Specifically, under ST, the increase in motor symptoms explains a decrease in spatio-temporal walking parameters, e.g., gait speed, which is also consistent with previous studies ( 14 , 75 ). Moreover, our results suggest that patients with a walking aid are more affected by the underlying disease.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, the mean values of gait velocity in this study were smaller than in healthy males [68] and correspond to normative data in early-stage PD during convenient walking [69]. We were thus able to confirm earlier findings from cross-sectional studies that showed a negative association between gait speed and (motor) disease stage in PD [69][70][71][72][73]. Analogously, larger sway areas at more severe disease stages have been described previously [74,75].…”
Section: Baseline Correlationssupporting
confidence: 91%
“…This association may be of precedential interest for future clinical decisionmaking (see below). It has already been shown that PD per se [76], advanced disease stage [69,70], PIGD phenotype [77], medication OFF states [78][79][80], and dual-tasking with cognitive load [81][82][83][84] are associated with shortened step and stride lengths. Dual-tasking abilities are particularly relevant to daily life and may predict daily functioning in PD [85].…”
Section: Baseline Correlationsmentioning
confidence: 99%
“…From this indicator, balance and cognitive function are impaired in the early stage of PD. Another study also found changes in SL as PD progressed, but they did not find changes in SL in the early stages of PD, which may be related to their relatively small sample sizes [ 29 ]. GV also deteriorates significantly as PD progresses, which also reflects the characteristics of bradykinesia in PD patients.…”
Section: Discussionmentioning
confidence: 99%